Room Temperature Electrodeposition of Ready-to-Use TiOx for Uniform p-n Heterojunction Over Nanoarchitecture - Cao, Yufeng; Qiao, Huajian; Zou, Yalong; An, Na; Zhou, Yang; Liu, Deyu; Kuang, Yongbo (Frontiers in Chemistry, 2022)
The photocathodes are essential in Photoelectrochemical systems for harvesting solar energy as green fuels. However, the light absorbing p-type semiconductor in them usually suffers from carrier recombination issues. An effective strategy to address it is fabricating the p-n heterojunction to create interfacial electric field. However, plenty of deposition process of n-type layer for this purpose requires either sophisticated instruments or subsequent treatments which may damage the vulnerable p-type structure. Herein, we report a mild approach for ready-to-use n-type layer with the full functionality. Structural analyses proved the successful coating of a uniform titania layer (up to 40 nm) over Cu2O without damaging its structure. Owing to the high Ti3+ content, the layer possesses excellent charge transport ability and requires no additional annealing. The heterojunction effectively facilitates the carrier separation and positively shifts the photocurrent onset potential for 0.2 V. Mott-Schottky, and the impedance study reveal an enhanced carrier collection with reduced charge transfer resistances. Such a nano-heterojunction can be further loaded with the hydrogen evolution catalyst which almost doubles the photocurrent with the extended lifetime than that of the pristine Cu2O nanoarray. This approach puts forward a potentially scalable and efficient choice for fabricating PEC devices.